Tegami bachi, Letter Bee. Volume 3, Meeting Sylvette Suede - Asada, Hiroyuki, 1968- (Viz Media, 2010)
Lag almost breaks the record time on his Letter Bee test, securing a job as a Letter Bee! His celebration ends with unwelcome news: the record holder, his hero Gauche Suede, is no longer a Letter Bee! Shocked, Lag seeks out Gauche's little sister Sylvette to learn exactly what happened. Sylvette has no answers, only memories and a broken heart.